Development and Challenge of SDN/NFV - Huiling, Zhao; Fan Shi (Dianxin kexue)
The cloud network is the trend of the telecom world now. As the key technology, SDN and NFV get so much attention from everyone. Not only the standard organization but also the other stakeholders do many contributions to the development of SDN/NFV. Opposite to its rapid steps, SDN/NFV still have to face some challenges, such as the security, interoperation and performance issue, which should be the new technical focus.